Faktor-faktor yang memengaruhi seksualitas pada perempuan dengan HIV: Telaah sistematis - Sari, Levi Anggriani Purnama; Afiyanti, Yati; Susanti, Suryane Sulistiana; Rachmawati, Imami Nur (Program Studi Ilmu Keperawatan-fakultas Ilmu Kesehatan Universitas Malahayati, 2025)
Background: Sexuality is part of basic human needs that has not received attention and is considered less important, both in social services and in care. There are several factors that influence sexuality in women with HIV, such as the interaction of biological, psychological, social, economic, political, cultural, legal, historical, religious and spiritual factors. Purpose: To identify and analyze various factors that influence sexuality in women with HIV. Method: A systematic review of cross-sectional and cohort studies was conducted in September 2024 using 6 databases, namely Clinicalkey, Clinicalkey Nursing, Scopus, ScienceDirect, SpringerLink, Proquest, and Taylor & Francis. The keywords used were